Steroid-Induced Osteonecrosis of the Femoral Head: Novel Insight Into the Roles of Bone Endothelial Cells in Pathogenesis and Treatment - Huang, Cheng; Wen, Zeqin; Niu, Junjie; Lin, Subin; Wang, Weiguo (Frontiers in Cell and Developmental Biology, 2021)
Steroid-induced osteonecrosis of the femoral head (SONFH) is a disease characterized by the collapse of the femoral head. SONFH occurs due to the overuse of glucocorticoids (GCs) in patients with immune-related diseases. Among various pathogenesis proposed, the mechanism related to impaired blood vessels is gradually becoming the most convincing hypothesis. Bone endothelial cells including bone microvascular endothelial cells (BMECs) and endothelial progenitor cells (EPCs) play a crucial role in the maintenance of vascular homeostasis. Therefore, bone endothelial cells are key regulators in the occurrence and progression of SONFH. Impaired angiogenesis, abnormal apoptosis, thrombosis and fat embolism caused by the dysfunctions of bone endothelial cells are considered to be the pathogenesis of SONFH. In addition, even with high disability rates, SONFH lacks effective therapeutic approach. ICA, pravastatin, and VO-OHpic are candidate reagents to prevent and treat SONFH through improving above pathological processes. However, these reagents are still in the preclinical stage and will not be widely used temporarily. In this case, bone tissue engineering represented by co-transplantation of bone endothelial cells and bone marrow mesenchymal stem cells (BMSCs) may be another feasible therapeutic strategy.